Temperature-dependent feedbacks drive the pattern of Antarctic temperature change - Bradley R. Markle; Eric J. Steig (Proceedings of the National Academy of Sciences, 2026)
Antarctica is an important component of the Earth’s climate system. Here we investigate temperature change in Antarctica across a range of timescales, from millennial to orbital, over the last 4 × 10 5 y, using a compilation of ice-core water-isotope records. We identify a persistent pattern of change in which the temperature variability of an Antarctic site increases with its mean surface temperature. When the entire continent warms, the warmest parts of Antarctica warm more; when the entire continent cools, the warmest parts cool more. This pattern is inconsistent with the Planck response, the simplest possible null hypothesis for Antarctic temperature change. However, a temperature-dependent feedback explains the fundamental pattern of temperature change. The feedback arises from a nonlinearity of the greenhouse effect, evident only at the cold surface temperatures of the Antarctic. This feedback may be initiated by any mean energetic forcing and thus manifests across all timescales. Local deviations from the expected pattern of temperature change indicate regional forcing such as changes in ice-sheet elevation. We reconstruct the surface elevation of the main ice divide in West Antarctica over the last deglaciation, finding a history that is supported by geological and glaciological evidence and consistent with ice-sheet modeling.